2018
DOI: 10.1103/physrevx.8.021052
|View full text |Cite
|
Sign up to set email alerts
|

Displacemon Electromechanics: How to Detect Quantum Interference in a Nanomechanical Resonator

Abstract: We introduce the "displacemon" electromechanical architecture that comprises a vibrating nanobeam, e.g., a carbon nanotube, flux coupled to a superconducting qubit. This platform can achieve strong and even ultrastrong coupling, enabling a variety of quantum protocols. We use this system to describe a protocol for generating and measuring quantum interference between trajectories of a nanomechanical resonator. The scheme uses a sequence of qubit manipulations and measurements to cool the resonator, to apply tw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 83 publications
(161 reference statements)
0
61
0
Order By: Relevance
“…These quantities can then be used to give a measure of the effectiveness of the cat-state storage and retrieval. The signatures we examine are the fringe patterns in quadrature probability distributions [41,42], the Wigner function [16,26,27,53] and its negativity [41,45], the off-diagonal terms of the density operator [16], and a variance signature [54][55][56][57][58][59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%
“…These quantities can then be used to give a measure of the effectiveness of the cat-state storage and retrieval. The signatures we examine are the fringe patterns in quadrature probability distributions [41,42], the Wigner function [16,26,27,53] and its negativity [41,45], the off-diagonal terms of the density operator [16], and a variance signature [54][55][56][57][58][59][60][61][62].…”
Section: Introductionmentioning
confidence: 99%
“…High quality nano(micro)-mechanical resonator is one of the best testbed for fundamental physics [1], such as the macroscopic quantum superpositions [2,3], the gravity induce wavefunction collapse [4], the boundary between quantum and classical regimes [5,6], and etc. It is found that the large quantum superpositions of the nano-mechanical resonator could be realized with the help of cavity modes [7], superconducting circuits [8,9], nitrogen-vacancy centers [10][11][12][13], and etc. The quantum-classical boundaries can be tested in these systems through matter-wave interferometry [8,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…A similar time dependent coupling was considered in Ref. [4] by using an external magnetic field. From Fig.…”
Section: Modelmentioning
confidence: 93%
“…Ignoring the oscillating terms is the rotating wave approximation [59] and is valid for time scales longer than the mechanical period t ω −1 m as the second two terms average out and (almost) vanish 4 . This interaction generates a two mode squeezed state between the optical field and mechanical oscillator and can be used to entangle the light and the mechanical motion [67,68,69,70].…”
Section: The Rotating Framementioning
confidence: 99%
See 1 more Smart Citation